Design, Construction, and Evaluation of an Air Filtration System Based on a Nanofiber Filter Containing a Metal-Organic Framework for the Removal of Aerosols Emitted from CNC Machining Operations - Mehrdad Helmi Kohnehshahri; Farideh Golbabaei; Somayeh Farhang Dehghan; Rezvan Zendehdel; Alireza Abbasi; Zahra Yadegar (بهداشت و ایمنی کار, 2025)
Introduction: With the advancement of industries and increased use of metalworking fluids, controlling pollutants generated by machining operations has become increasingly challenging. This study aimed to address these challenges by designing an air filtration system designed specifically for this purpose. Material and Methods: A local exhaust ventilation system was developed based on the VS-80-12 ACGIH standard, tailored to the working conditions and air sampling of the environment. The filtration system includes an aluminum pre-filter, an E11 class filter, and a nanofiber filter incorporating a metal-organic framework. The performance of the system was evaluated by measuring the numerical concentration of particles and the mass concentration of oil mist at both the inlet and outlet. The results were then compared to those obtained from an E1 class filter. Results: The results obtained from XRD and FTIR analyses showed that ZIF-8 had high crystallinity and was successfully incorporated into the structure of the fibrous media filter containing metal-organic framework. The evaluation revealed that the filtration system effectively removed pollutant particles at their source. Notably, the initial efficiency for larger particles reached 100%, while the average removal efficiency for particles smaller than 2.5 microns was 99%. Conclusion: In conclusion, the combination of nanofiber filters with a metal-organic framework and aluminum pre-filters presents an effective solution for controlling particulate pollutants from machining operations. However, further research is necessary to comprehensively assess the system’s performance, particularly regarding dust loading capacity. Future studies should also explore the effects of various factors, such as airflow rate and the type of metalworking fluid, on the system’s efficacy.